ANALISIS KOMPILASI HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK MUAMALAH PADA PEMBELIAN BUAH MANGGA DENGAN SISTEM TEBAS - anik nur ria (Minhaj: Jurnal Ilmu Syariah, 2021)
Humans cannot be separated from buying and selling activities. Buying and selling is a social activity that provides reciprocity. In fiqh there is a prohibition against buying and selling using the slash system. However, there are scholars who allow the sale and purchase of slash, by following several conditions. For this reason, this research aims to reveal the buying and selling of the slash system allowed by the Ulama by explaining the legal basis, terms, and exposure of the slash system buying and selling transactions. This study used a qualitative approach with a compilation analysis of sharia economic law on muamalah practices in purchasing mangoes using the slash system.